Interactive leadership in turbulent school climates. An exploratory study of high school principals from the City of Buenos Aires. (March 2018) - Romero, Claudia; Krichesky, Gabriela
School leadership has been identified as a key function to assuring quality in education. Principals' leadership can have a direct effect on students' learning by improving teaching, or an indirect effect by creating conditions that foster learning. This exploratory study aims to understand how school principals exercise their leadership and its relation with the learning climate of their schools. We analyzed two dimensions: principals' agendas and school climate perception, using the questionnaire provided by the TALIS examination, in a sample of 82 principals from secondary schools in the City of Buenos Aires. Administrative and leadership tasks and meetings occupy first place in the agenda of the principals from our sample. However, principals devote almost half of their time to interactions with non-teacher members of the school community. This suggests the preponderance of an " interactive leadership ", which appears as a response towards "turbulent school climates". Nevertheless, it is precisely the instructional role of principals that can effectively improve learning conditions by operating on the academic dimension of school climate. This requires training policies and professional development opportunities that improve the instructional role of school leaders so that they can develop a more proactive leadership.